2015
DOI: 10.1111/trf.13125
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties in hematopoietic progenitor cell collection from a patient with TEMPI syndrome and severe iatrogenic iron deficiency

Abstract: HPC-A collection from a patient with TEMPI syndrome was complicated by microcytic erythrocytosis, leading to RBC contamination and hemolysis in the product. Adequate HPCs were collected and the patient tolerated infusion without RBC depletion or washing. Our report highlights difficulties of HPC-A collection from iron-deficient patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Due to the pathogenesis of TEMPI syndrome, the treatment strategies are generally similar to those for multiple myeloma. Bor is one of the most frequently used treatments for TEMPI syndrome [1,[4][5][6][7][20][21][22]. Although most cases can be successfully treated with Bor, some cases are refractory to PI [8,13].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the pathogenesis of TEMPI syndrome, the treatment strategies are generally similar to those for multiple myeloma. Bor is one of the most frequently used treatments for TEMPI syndrome [1,[4][5][6][7][20][21][22]. Although most cases can be successfully treated with Bor, some cases are refractory to PI [8,13].…”
Section: Discussionmentioning
confidence: 99%
“…Some patients with TEMPI syndrome have required wheelchairs and continuous supplemental oxygen because of their progressive hypoxia ( 5 , 6 ). However, some patients with TEMPI syndrome have not had right-to-left shunting at their first presentation ( 7 , 8 ), possibly because the characteristic manifestations progress slowly over several years.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Of note, we found all the 3 patients had the clinical characteristics of peritoneal fluid and pleural effusion (supplemental Table 5), and previous studies also showed that 5 patients with TEMPI syndrome exhibited peritoneal fluid or pleural effusion. [15][16][17][18][19] In this study, we also found that the level of serum MIF in patient 1 was significantly decreased after treatment with the VCD regimen, which was changed in accordance with the downtrend of PCs, M-protein, hemoglobin, erythropoietin, and the improvement of telangiectasias, perinephric fluid collections, and intrapulmonary shunting (Figure 2E). These studies revealed a possible role of MIF in the development of intrapulmonary shunting, telangiectasias, elevated erythropoietin levels, and perinephric fluid collections, and furthermore, with the association between MIF levels and response to treatment in our patient, supporting that the duplication of 22q11.23 and upregulation of MIF in the monoclonal PCs may be involved in the pathophysiology of TEMPI syndrome.…”
Section: Resultsmentioning
confidence: 65%